Postsynaptic Receptors for Amyloid-β Oligomers as Mediators of Neuronal Damage in Alzheimer’s Disease - Dinamarca, Margarita C.; Ríos, Juvenal A.; Inestrosa, Nibaldo C. (Frontiers in Physiology, 2012)
The neurotoxic effect of amyloid- peptide (Aβ) over the central synapses has been described and is reflected in the decrease of some postsynaptic excitatory proteins, the alteration in the number and morphology of the dendritic spines and a decrease in long- term potentiation (LTP). Many studies has been carried out to identify the putative Aβ receptors in neurons, however is still no clear why the Aβ oligomers affect only the excitatory synapse. Aβ oligomers bind to neurite and preferentially to the postsynaptic region, where the postsynaptic protein-95 (PSD-95) is present in the glutamatergic synapse. This protein through its PDZ domain interacts directly with the NMDA receptor and the adhesion protein neuroligin (NL). Neuroligin is a postsynaptic protein which binds to the presynaptic protein, neurexin (NRX) to form a heterophilic adhesion complex, involved in the establishment of pre- and postsynaptic regions. Therefore, the disruption of this interaction affects the integrity of the synaptic contact. NL-1, 3 and 4 are enriched to the excitatory synapse, while the NL-2 is found mainly in the inhibitory synapse. Structurally, NL has an extracellular domain homolog to acetylcholinesterase (AChE), the first synaptic protein that was found to interact with Aβ. In the present review we will document the interaction between Aβ and the extracellular domain of NL-1 at the excitatory synapse, as well as the interaction with other postsynaptic components, including the glutamatergic receptors (NMDA and mGluR5), prion protein, neurotrophin receptor and the 7-nicotinic acetylcholine receptor (7-nAChR). We conclude that several new Aβ oligomers receptors exist at the excitatory synapse, which could be the responsible of the neurotoxic effect described for the Aβ oligomers. The characterization of the interaction between Aβ receptors and Aβ oligomers could help to understand the source of the neurologic damage observed in the brain of the Alzheimer’s disease patients.